P19-S Can nerve conduction studies help to distinguish motor CIDP and MMN?. Issue 7 (July 2019) - Lipowska, Marta; Barańska, Judyta; Gaweł, Małgorzata; Potulska-Chromik, Anna; Kostera-Pruszczyk, Anna
Abstract : Motor chronic inflammatory demyelinating polyneuropathy (CIDP) and multifocal motor neuropathy (MMN) share exclusively motor peripheral nerves involvement. Differentiation is based mainly on clinical symptoms, but sometimes it can be difficult. The aim was electrophysiological evaluation of motor CIDP and MMN patients according to frequency of conduction block (CB) and demyelination. Material and methods: retrospective analysis of nerve conduction studies (NCS) of patients fullfiling EFNS/PNS criteria for definite or probable CIDP or MMN, diagnosed in our department, was used. EFNS/PNS criteria for CIDP were applied to define demyelination and CB. 13 patients were included: 6 with motor CIDP, 7 with MMN; in CIDP there were 2M and 4F, age 21–70 yrs, mean 41.3 yrs, in MMN 3 M and 4F, age 34–61 yrs, mean 43.7 yrs. 6–8 motor nerves were examined in every patient, nerves with amplitude of compound motor action potential (CMAP) <1 mV were excluded. Results: At least one CB was found in every CIDP and MMN patient. Number of CB per segment was 0, 18 in CIDP and 0, 20 in MMN. Conduction velocity (CV) reduction was revealed in 1 CIDP patient in 3 segments and in 4 MMN patients in 1–2 segments (segments with CB and entrapment sites were excluded). Distal CMAP duration increase was found in at least one nerve in every CIDP patient (in 1–5 nerves, mean 2, 5) and in 2 MMN patients in 1–2 nerves. Conclusion: NCS alone can not distinguish CIDP from MMN, although it seems that distal CMAP duration increase is more common feature in CIDP.